Integration of segmented microflow chemistry and online HPLC/MS analysis on a microfluidic chip system enabling enantioselective analyses at the nanoliter scale. Issue 13 (19th May 2021) - Piendl, Sebastian K.; Schönfelder, Thomas; Polack, Matthias; Weigelt, Laura; van der Zwaag, Till; Teutenberg, Thorsten; Beckert, Erik; Belder, Detlev
Abstract : In this work, we introduce an approach to merge droplet microfluidics with an HPLC/MS functionality on a single chip to analyze the contents of individual droplets. Abstract : In this work, we introduce an approach to merge droplet microfluidics with an HPLC/MS functionality on a single chip to analyze the contents of individual droplets. This is achieved by a mechanical rotor–stator interface that precisely positions a microstructured PEEK rotor on a microfluidic chip in a pressure-tight manner. The developed full-body fused silica chip, manufactured by selective laser-induced etching, contained a segmented microflow compartment followed by a packed HPLC channel, which were interconnected by the microfluidic PEEK rotor on the fused silica lid with hair-thin through-holes. This enabled the targeted and leakage-free transfer of 10 nL fractions of droplets as small as 25 nL from the segmented microflow channel into the HPLC compartment that operated at pressures of up to 60 bar. In a proof of concept study, this approach was successfully applied to monitor reactions at the nanoliter scale and to distinguish the formed enantiomers.